Implementasi Manajemen Kesiswaan Dalam Meningkatkan Prestasi Siswa di MA NW Nurul Iman Keruak - Rizqi Maulita; Syahdan; Abdurrahim (Lembaga Pendidikan Al-Gafari, 2023)
Management participant educates its very existence is needed in educational institutions because students' or participants' education is subject to the transformation process of knowledge and skills. Success in administration education depends on the development potency physical. Intelligence intellectual, social, emotional mental participants educate. The research objective is to know implementation management students in increasing achievements at Madrasah Aliah NW Nurul Iman Keruak. Study This uses study type qualitative with take location at MA NW Nurul Iman Keruak. Data collection was carried out with the use of methods of observation, interview, and documentation. Subject researcher in study This is The principal of the madrasa, Deputy Student Affairs, as well subject supporters are teachers, coaches extracurricular activities, and students at MA NW Nurul Iman Keruak. Engineering Data analysis was performed in a manner interactive and ongoing in a manner Keep going continuously until complete so until data saturation. examination data validation is carried out with data triangulation. Result of the study This finds that Implementation Management Student at MA NW Nurul Iman Keruak is Already ok. those results can be seen from planning participant educate includes acceptance participant education just done nationally by the next Ministry of Religion of the Republic of Indonesia stage second carried out in the respective Kanwil up to the determination of graduation student new is the result can see from line online, do activity coaching studentship, besides it's MA NW Nurul Iman Keruak has obtained achievements the best through activity extracurricular nor extracurricular.